2013
DOI: 10.1073/pnas.1308381110
|View full text |Cite
|
Sign up to set email alerts
|

Multiscaled exploration of coupled folding and binding of an intrinsically disordered molecular recognition element in measles virus nucleoprotein

Abstract: Numerous relatively short regions within intrinsically disordered proteins (IDPs) serve as molecular recognition elements (MoREs). They fold into ordered structures upon binding to their partner molecules. Currently, there is still a lack of in-depth understanding of how coupled binding and folding occurs in MoREs. Here, we quantified the unbound ensembles of the α-MoRE within the intrinsically disordered C-terminal domain of the measles virus nucleoprotein. We developed a multiscaled approach by combining a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 101 publications
(173 reference statements)
6
125
0
Order By: Relevance
“…In the present work, we have found that skMLCK and CaM have similar properties in their mixturebinding pathways. In addition, we found the skMLCK binding peptide gradually forms α-helical structures binding to CaM, which is in accordance with a "divide-and-conquer" mechanism proposed for the IDP binding-folding (54). In a word, we find many interesting intrinsically disordered properties of skMLCK during its binding process with CaM in our work.…”
Section: Binding Process Involves Both the Local And Global Conformatsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present work, we have found that skMLCK and CaM have similar properties in their mixturebinding pathways. In addition, we found the skMLCK binding peptide gradually forms α-helical structures binding to CaM, which is in accordance with a "divide-and-conquer" mechanism proposed for the IDP binding-folding (54). In a word, we find many interesting intrinsically disordered properties of skMLCK during its binding process with CaM in our work.…”
Section: Binding Process Involves Both the Local And Global Conformatsupporting
confidence: 88%
“…To extend a SBM to systems with two basins, we integrated information of the open (PDB ID: 1CLL) and closed (PDB ID: 2BBM) structures by a mixed-contact map model (10,13,32,60,61). Because the charged interactions and the hydrophobic interactions play an important role in in CaM recognition (13,15,25,(29)(30)(31)54), we added the electrostatic interactions and hydrophobic interactions in our SBM. The electrostatic potential is represented by the Debye-Huckel model (64).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, computational studies on IDP-protein interactions, 52 including that between ACTR and NCBD, 67 30 and ACTR/NCBD (ca.…”
Section: Coupled Binding and Downhill Foldingmentioning
confidence: 99%
“…The development of atomic-resolution models requires, however, complementation of experimental data by computational simulations. Theoretical approaches have been improved to effectively model disordered conformational ensembles based on structural information derived from native mass spectrometry and other biophysical analyses [28][29][30].…”
Section: Introductionmentioning
confidence: 99%